A Tiny, Counterintuitive Change to the Mathematics of the Schrodinger Wave Packet and Quantum ElectroDynamics Could Vastly Simplify How We View Nature - Boyd, Jeffrey (JOURNAL OF ADVANCES IN PHYSICS, 2020)
This article proposes that an unexpected approach to the mathematics of a Schro ̋dinger wave packet and Quantum Electro-Dynamics (QED), could vastly simplify how we perceive the world around us. It could get rid of most if not all quantum weirdness. Schro ̋dinger’s cat would be gone. Even things that we thought were unquestionably true about the quantum world would change. For example, the double slit experiment would no longer support wave particle duality. Experiments that appeared to say that entangled particles can communicate instantaneously over great distances, would no longer say that. Although the tiny mathematical change is counterintuitive, Occam’s razor dictates that we consider it because it simplifies how we view Nature in such a pervasive way. The change in question is to view a Schro ̋dinger wave packet as part of a larger Elementary Wave traveling in the opposite direction. It is known in quantum mechanics that the same wave can travel in two countervailing directions simultaneously. Equivalent changes would be made to QED and Quantum Field Theory. It is known in QM that there are zero energy waves: for example, the Schro ̋dinger wave carries amplitudes but not energy.